Outcome predictors in patients with juvenile idiopathic arthritis receiving intraarticular corticosteroid therapy - Anindya Diwasasri; Sumadiono Sumadiono; Sri Mulatsih (Paediatrica Indonesiana, 2019)
Background Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in children. It can continue into adulthood and cause severe joint damage, resulting in disability and decreased quality of life. Objective To determine the predictors of clinical outcomes in JIA patients receiving intra-articular corticosteroid injections (IACS). Methods We conducted a retrospective cohort study of children with JIA receiving IACS therapy in Dr. Sardjito General Hospital from 1 January 2012 to 31 December 2017 by reviewing data from medical records. The dependent variables were disabilities and early remission time. Independent variables included age at diagnosis, JIA subtype, duration of disease at first diagnosis, timing of IACS, exposure to oral systemic therapy, as well as anti-nuclear antibodies (ANA), rheumatoid factor (RF), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) test results. External variables were gender and nutritional status. Results Of 36 patients who received intraarticular corticosteroid injections, 28 (77.8%) experienced remission, and 16 (50%) experienced disabilities. Female subjects (OR 5.296; 95%CI 1.143 to 24.548; P=0.027) and subjects with ESR >26 mm/h (OR 2; 95%CI 1.259 to 3.170; P=0.043) were more likely to have disabilities. Use of oral corticosteroids for ≤3 months and IACS treatment ≤ 3 months after diagnosis were predictors of early remission time (OR 6.897; 95%CI 1.869 to 25 and OR 3.290; 95%CI 1.195 to 9.091, respectively). However, only oral corticosteroid had a significant correlation in multivariate analysis. Conclusion Female gender and ESR > 26 mm/h predict disabilities in JIA patients receiving IACS. Duration of oral corticosteroid ≤3 months and early IACS within 3 months of diagnosis correlate to earlier remission time. Shorter duration of oral corticosteroid is the only significant predictor for earlier remission time in JIA patients receiving IACS therapy.